Answer:
16.4
Step-by-step explanation:
If it is asking for the tenth it will be the 1st one after the point and you round it to the next one.
Answer:
If all the dimensions of the rectangular pyramid are multiplied by 1/5, the volume will be 125 times smaller.
Step-by-step explanation:
A rectangular pyramid has the following dimensions:
length(l), height(h) and width(w)
The volume is:
![V = \frac{l*h*w}{3}](https://tex.z-dn.net/?f=V%20%3D%20%5Cfrac%7Bl%2Ah%2Aw%7D%7B3%7D)
If all the dimensions of the rectangular pyramid are multiplied by 1/5
Then we have that:
![l = \frac{l}{5}, w = \frac{w}{5}, h = \frac{h}{5}](https://tex.z-dn.net/?f=l%20%3D%20%5Cfrac%7Bl%7D%7B5%7D%2C%20w%20%3D%20%5Cfrac%7Bw%7D%7B5%7D%2C%20h%20%3D%20%5Cfrac%7Bh%7D%7B5%7D)
The modified volume will be:
![V_{M} = \frac{\frac{l}{5}*\frac{w}{5}*\frac{h}{5}}{3} = \frac{\frac{l*w*h}{125}}{3} = \frac{l*h*w}{125*3} = \frac{1}{125}(\frac{l*h*w}{3}) = \frac{V}{125}](https://tex.z-dn.net/?f=V_%7BM%7D%20%3D%20%5Cfrac%7B%5Cfrac%7Bl%7D%7B5%7D%2A%5Cfrac%7Bw%7D%7B5%7D%2A%5Cfrac%7Bh%7D%7B5%7D%7D%7B3%7D%20%3D%20%5Cfrac%7B%5Cfrac%7Bl%2Aw%2Ah%7D%7B125%7D%7D%7B3%7D%20%3D%20%5Cfrac%7Bl%2Ah%2Aw%7D%7B125%2A3%7D%20%3D%20%5Cfrac%7B1%7D%7B125%7D%28%5Cfrac%7Bl%2Ah%2Aw%7D%7B3%7D%29%20%3D%20%5Cfrac%7BV%7D%7B125%7D)
So
If all the dimensions of the rectangular pyramid are multiplied by 1/5, the volume will be 1/125 of the original, that is, 125 times smaller.
Each pair of pants cost $27. Set up a system of equations.
5t + 5p = 220
5t + p = 112
Subtracting the second equation from the first,
4p = 108
p =27
Answer:
45 m
Step-by-step explanation:
Here,
Base (b) = 9m
Height (h) = 5m
Area of parallelogram = b * h. = 9*5. = 45m
The graph is a straight line graph with a slope of -1/2
Equation of a line in point-slope form
The equation of a line in point slope form is expressed as:
y - y₁ = m(x - x₁)
Given the following parameters
Point = (-2, 3)
Slope = -1/2
Substitute the given parameters into the formula
y-3 = -1/2(x-(-2))
y-3 = -1/2(x+2)
Write in slope-intercept form
2(y-3) = -(x+2)
2y-2(3) = -x -2
2y - 6 = -x -2
2y = -x + 4
y = -1/2x + 2
The graph of the equation is as shown below
Learn more on equation of a line here: brainly.com/question/18831322
#SPJ1